Community Sport and the Politics of Aging: Co-design and Partnership Approaches to Understanding the Embodied Experiences of Low-Income Older People - Mansfield, Louise; Kay, Tess; Anokye, Nana; Fox-Rushby, Julia (Frontiers in Sociology, 2019)
The promotion of physical activity for older people is dominated by biomedically informed polices emphasising the prescription of exercise as medicine and a universal approach to the promotion of active ageing in later life. Yet, more recent research recognises that being physically active in later life is complex and contested, shaped by the intersections of biological, psychological and sociological experiences, and requires differentiated responses that address this complexity. There is a disconnect between research, policy and the physical activity experiences of older people which leads to over-generalised policy and practice in the promotion and delivery of community sport to older people. This paper presents findings from a complex community sport project employing a coproduction framework with low income older age people. Participatory community approaches including focus group discussions, and extended observations and informal conversations throughout the project develop understanding of the complexities of ageing and community sport engagement among older people with limited income. Three themes are identified and discussed: (1) lived experience, ageing bodies and the changing dynamics of involvement in sport and exercise in the life course, (2) embodying ageing - moving beyond practical barriers for understanding ageing, lived experience and being physically active, and (3) corporeal pleasures of older sporting bodies. The paper concludes that there is a need to explore the significance of locally specific public knowledge from older people which directly addresses the complexity and inequalities of individuals’ everyday lives in their communities; lived experiences likely to impact on preferences for, engagement in, and enjoyment of physical activity.